2020
DOI: 10.1021/acs.energyfuels.0c03443
|View full text |Cite
|
Sign up to set email alerts
|

Production Behaviors of Water-Saturated Methane Hydrate Deposits during the Depressurization with/without Thermal Water Compensation Process

Abstract: Marine methane hydrate is an important source of energy for the future, attracting great attention of global researchers and many governments. The water-saturated hydrate deposit is more similar to the real environment of marine sediments. Yet, the production behaviors during the depressurization with/without thermal water compensation process are still unclear. In this study, the water-saturated hydrate deposits with initial conditions of 6 MPa, 3 °C, and 20% hydrate saturation are remolded. The basic decompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…However, immature exploitation technologies limit the widespread utilization of this energy source. How to promote the dissociation of methane hydrate in sediments and recover methane gas safely and effectively has been the focus of research in recent years. …”
Section: Introductionmentioning
confidence: 99%
“…However, immature exploitation technologies limit the widespread utilization of this energy source. How to promote the dissociation of methane hydrate in sediments and recover methane gas safely and effectively has been the focus of research in recent years. …”
Section: Introductionmentioning
confidence: 99%
“…There are six reviews covering a wide range of aspects related to methane hydrates targeting resource potential, production methods (depressurization and CH 4 /CO 2 exchange), exploration activities, sand management, and hydrate properties . The original research articles pertaining to the topic of hydrates cover a wide spectrum of areas, from numerical modeling, ,,, hydrate properties and characterization, ,,,, hydrate equipment ,,, to fluid production analysis, , ,, etc.…”
Section: Hydratementioning
confidence: 99%
“…There is a positive exponential relationship between the temperature and the pressure of the hydrate phase equilibrium line . Zheng et al found that the thermodynamic p – T curve of hydrate decomposition is also similar to the phase equilibrium line . In addition, the decomposition of hydrates is an endothermic reaction, and thus, the heat transfer from sediment outside provides a continuous impetus for hydrate decomposition .…”
Section: Introductionmentioning
confidence: 95%
“…18 Zheng et al found that the thermodynamic p−T curve of hydrate decomposition is also similar to the phase equilibrium line. 19 In addition, the decomposition of hydrates is an endothermic reaction, 20 and thus, the heat transfer from sediment outside provides a continuous impetus for hydrate decomposition. 21 Li's research group revealed the heat transfer law of sediments during the NGH decomposition process by depressurization.…”
Section: Introductionmentioning
confidence: 99%